The relationship of dyslipidemia and insulin resistance in patients with type 2 diabetes and the metabolic syndrome - Romaniv, Taras; Skrypnyk, Nadiya (ScienceRise: Medical Science, 2023)
The aim of the research was to study the relationship between dyslipidemia and insulin resistance in patients with type 2 diabetes with metabolic syndrome. Materials and methods: In accordance with the aim and objectives of the study, the group of subjects consisted of 120 patients with type 2 diabetes mellitus with MS who were undergoing inpatient treatment in the endocrinology department of the KNP "Regional Clinical Hospital of the Ivano-Frankivsk Regional Council" and 15 practically healthy individuals (PHI), who made up the control group. The degree of IR was determined by waist circumference (WC), IR indices: the HOMA-IR index and the Caro index. The distribution of patients with type 2 diabetes mellitus with MS and without signs of MS was carried out, depending on the presence of NASH. The concentration of endogenous insulin (EI) was determined by the enzyme immunoassay method using an autonomous chemiluminescence analyzer Maglumi 800 with a set of reagents Maglumi "Insulin" Shanghai International Holding Corp. GmbH (Europe), Hamburg, Germany. Glycated hemoglobin (HbA1c) was determined using the "Glycosylated Hemoglobin Spl" reagent of Granum Laboratory LLC, Kharkiv, Ukraine, using a ULAB 108UV spectrophotometer. The level of triglycerides and HDL-CHD in blood serum was determined with the help of the "Cholesterol Spl" reagent of the "Granum Laboratory" LLC, Ukraine, Kharkiv, using the ER 500 enzyme immunoassay analyzer. Results: calculation of generally accepted indices of insulin resistance, in particular the HOMA IR index, OT, BMI indicate the presence of significant insulin resistance in patients with type 2 diabetes with MS, while the changes were the greatest in patients with type 2 diabetes with MS and NASH. Insulin resistance syndrome contributes to lipid imbalance and is a metabolic prerequisite for the development of NASH. Conclusions. The results of the study are recommended for practical use in health care: correction of dyslipidemia against the background of glycemic control